2002
DOI: 10.1034/j.1399-3062.2002.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of histoplasmosis following allogeneic bone marrow transplant or solid organ transplant in a hyperendemic area

Abstract: Questions have arisen regarding the risk of developing symptomatic Histoplasma capsulatum infection among patients who undergo transplant-related immunosuppression in areas endemic for histoplasmosis. Our medical center is located in a hyperendemic area for histoplasmosis, where three large outbreaks occurred since 1978. We undertook a retrospective chart review of 137 patients who received allogeneic bone marrow transplant and of 449 patients who received solid organ transplant from January 1994 to December 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
72
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 9 publications
(13 reference statements)
4
72
2
1
Order By: Relevance
“…A study performed in Indianapolis, IN, at a medical center located in an area of hyperendemicity demonstrated that histoplasmosis is a rare infection following the immunosuppression of allogeneic bone marrow transplantation (BMT) or SOT (377). In this study, 18% of the recipients had CF titers that were positive for H. capsulatum, and chest X rays showed findings consistent with past histoplasmosis in 4% of the recipients.…”
Section: Infections Caused By Histoplasma Capsulatummentioning
confidence: 54%
See 1 more Smart Citation
“…A study performed in Indianapolis, IN, at a medical center located in an area of hyperendemicity demonstrated that histoplasmosis is a rare infection following the immunosuppression of allogeneic bone marrow transplantation (BMT) or SOT (377). In this study, 18% of the recipients had CF titers that were positive for H. capsulatum, and chest X rays showed findings consistent with past histoplasmosis in 4% of the recipients.…”
Section: Infections Caused By Histoplasma Capsulatummentioning
confidence: 54%
“…Some authors postulated that most of the posttransplant cases of histoplasmosis in areas of endemicity occur de novo during an outbreak and are not due to reactivation, and consequently, routine prophylactic antifungal therapy for the prevention of histoplasmosis following SOT cannot be recommended for these recipients (377). However, other authors believe itraconazole prophylaxis should be offered to recipients of organs from a seropositive donor.…”
Section: Infections Caused By Histoplasma Capsulatummentioning
confidence: 99%
“…However, Peddi et al reported 4 cases of renal transplant recipients that received intense immunosuppressive therapy in the 3 months prior to the onset of the infection (19). There are very low incidences of histoplasmosis among allogeneic-bone-marrowand solid-organ-transplant recipients, even in areas of hyperendemicity, and the risk of reactivation is also very low (23). This infection is very rare in our population.…”
mentioning
confidence: 89%
“…However, we were able to identify small mycobacterial colonies 3 days after incubation on chocolate agar plates, probably due to a very heavy inoculum. On microscopic examination, M. haemophilum usually appears as a short, beaded bacillus that may exhibit cording similar to that observed with Mycobacterium tuberculosis (13,19,23). Cord formation, or cording, is considered a virulence factor, first identified in M. tuberculosis.…”
mentioning
confidence: 94%
See 1 more Smart Citation